2022
DOI: 10.1093/ajh/hpab182
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings From a National Heart, Lung, and Blood Institute and the Centers for Disease Control and Prevention Workshop to Control Hypertension

Abstract: Hypertension treatment and control prevent more cardiovascular events than management of other modifiable risk factors. Although the age-adjusted proportion of US adults with controlled blood pressure (BP) defined as <140/90 mm Hg, improved from 31.8% in 1999–2000 to 48.5% in 2007–2008, it remained stable through 2013–2014 and declined to 43.7% in 2017–2018. To address the rapid decline in hypertension control, the National Heart, Lung, and Blood Institute and the Division for Heart Disease and Stroke P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…These CVH benefits associated with physical activity are applicable to a wide range of individuals. 45 Data presented in this section have also shown that some underresourced groups (eg, Black adults, adults in rural settings) who have poor CVH 30,49 also have low physical activity levels. 13 The intersection of low activity levels and poor CVH in underresourced groups highlights the potential for physical activity promotion to reduce CVH disparities.…”
Section: Physical Activity Levels By Risk Factors For Poor Cvhmentioning
confidence: 88%
“…These CVH benefits associated with physical activity are applicable to a wide range of individuals. 45 Data presented in this section have also shown that some underresourced groups (eg, Black adults, adults in rural settings) who have poor CVH 30,49 also have low physical activity levels. 13 The intersection of low activity levels and poor CVH in underresourced groups highlights the potential for physical activity promotion to reduce CVH disparities.…”
Section: Physical Activity Levels By Risk Factors For Poor Cvhmentioning
confidence: 88%
“…The authors discussed several constructive actions to reverse the decline in hypertension control, consistent with the October 2020 Call to Action to Control Hypertension by the US Surgeon General and explored more fully in another report. 7 Constructive action, supported by several key findings in the current report, 1 is imperative as cardiovascular events are rising in the US population. While the COVID-19 pandemic is beginning to ease, disparities in hypertension control were magnified during COVID-19.…”
mentioning
confidence: 64%
“…29 In addition, hypertension control may be improved through patient communications and community outreach tailored to engage individuals, promoting home blood pressure monitoring with clinical support, improving access to high-quality health care, and addressing social and financial barriers to hypertension control. [30][31][32]…”
Section: Discussionmentioning
confidence: 99%